PENERAPAN PENDEKATAN RECIPROCAL TEACHING DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 6 GUNUNG TALANG KABUPATEN SOLOK - Lusiana, Risa; Anggraini, Villia; Lovia, Lita (Pendidikan Matematika, 2013)
This research is motivated by the study understanding of mathematical concepts still lace. The aims of this research is for knowing the achievement of indicator of studentsâ understanding of mathematical concepts at eight grade by applying Reciprocal Teaching approach with quiz are better than studentsâ understanding mathematical concept by applying conventional learning in SMPN 6 Gunung Talang Solok Regency. The kind of this research is experiment research by random design towards subject. The population of this research is studentsâ who are at eight grade in SMPN 6 Gunung Talang in 2013/2014 academic years. The sample of the class which is chosen is VIIID class as the experiment class and VIIIB class as the control class. Form of the quiz and the test is essay and after result of the analysis questions and got the reliable question. Based on the hypothesis testing got P-value 0, 001 less from Î± that is 0,05. The conclusion of this research that is studentsâ understanding of mathematical concept by applying Reciprocal Teaching approach with quiz are better than studentsâ understanding mathematical concept at eight class in SMPN 6 Gunung Talang Solok Regency.